(untitled) (Ustozlar uchun, 2026)
This article examines the theoretical and practical frameworks of teaching reading techniques and strategies in the context of foreign language acquisition. The research provides a comparative analysis of modern methods such as Skimming, Scanning, and the SQ3R system, evaluating their effectiveness in enhancing student comprehension. It explores the relationship between text typology and strategic selection, offering pedagogical recommendations to minimize cognitive load while maximizing critical thinking. Furthermore, the article addresses the transition from mechanical word-recognition to high-level information synthesis, incorporating cognitive psychology models and metacognitive awareness.